Assessing the heat sensitivity of Urdbean (Vigna mungo L. Hepper) genotypes involving physiological, reproductive and yield traits under field and controlled environment - Chaudhary, Shikha; Jha, Uday Chand; Paul, Pronob J.; Prasad, P. V. Vara; Sharma, Kamal Dev; Kumar, Sanjeev; Gupta, Debjyoti Sen; Sharma, Parul; Singh, Sarvjeet; Siddique, Kadambot H. M.; Nayyar, Harsh (Frontiers Media, 2022)
The rising temperatures are seriously impacting the food crops, including urdbean; hence efforts are needed to identify the sources of heat tolerance in such crops to ensure global food security. In the present study, urdbean genotypes were evaluated for heat tolerance under natural outdoor for two consecutive years (2018, 2019) and subsequently in the controlled environment of the growth chamber to identify high temperature tolerant lines. The genotypes were assessed involving few physiological traits (membrane damage, chlorophyll, photosynthetic efficiency, stomatal conductance, lipid peroxidation), reproductive traits (pollen germination % and pollen viability %) and yield related traits (total number of pods plant-1, total seeds plant-1, single seed weight and seed yield plant-1). Based upon these tested traits, PantU31, Mash114, UTTARA and IPU18-04 genotypes were identified as promising genotypes for both years under heat stress condition. Further confirming heat tolerance, all these four tolerant and four sensitive genotypes were tested under controlled environment under growth chamber condition. All these four genotypes PantU31, Mash114, UTTARA and IPU18-04 showed high chlorophyll content, photosynthetic efficiency, stomatal conductance, leaf area, pods plant-1, total seeds plant-1 and low reduction in pollen germination % and pollen viability under stress heat stress condition. Moreover, yield and yield related traits viz., pods plant-1, seeds plant-1, single seed weight and seed yield plant-1 showed very strong positive correlation with pollen germination and pollen viability except electrolyte leakage and malondialdehyde content. Thus, these genotypes could be potentially used as donors for transferring heat tolerance trait to the elite yet heat-sensitive urdbean cultivars.